Senile cataract — features of development and outcomes of surgical treatment in patients with hepatitis B and C viruses - B.N. Hatsukova; G.M. Chernakova; S.A. Kochergin; E.A. Kleshcheva; E.Yu. Malinnikova; K.K. Kyuregyan; M.M. Mikhailov (РМЖ "Клиническая офтальмология", 2019)
B.N. Hatsukova1, G.M. Chernakova2, S.A. Kochergin1, E.A. Kleshcheva1, E.Yu. Malinnikova1,  K.K. Kyuregyan3, M.M. Mikhailov3 1 Russian Medical Academy of Continuing Professional Education, Moscow, Russian Federation 2 S. Fyodorov Eye Microsurgery Federal State Institution, Moscow, Russian Federation  3 Scientific Research Center of Russian Medical Academy of Continuing Professional Education,   Moscow, Russian Federation Aim: to analyze features of the clinical course and results of the surgical treatment of cataracts in patients with chronic hepatitis B and C, to search for possible relationships between the formation of cataracts and the fact of chronic infection caused by HBV/HCV. Patients and Methods: 20 patients were included in the study. The main group consisted of 10 patients with HBV and HCV. The experimental group (control group) consisted of 10 patients with the absence of diagnostically significant levels of antibodies to HBV and HCV in blood serum. All patients in both groups twice underwent a standard ophthalmologic examination, as well as optical coherence tomography (OCT) of the macular area and optic disc, Humphrey Visual Field, and visocontrastometry. Cataract extraction was performed using Laureate phacoemulsifier. All patients were implanted with a posterior chamber intraocular lens (IOL). The levels of biochemical indicators of the functional state of the liver — alanine aminotransferase (ALAT) and aspartate aminotransferase (ASAT) — were determined for all patients. Results: average age of patients in the main group was 61.9±5.23 years, in the control group — 69.4±3.12. The average level of ALAT in the group with patients infected with hepatitis viruses was 44.5±4.54 U/l, and in the group of healthy people — 22.45±2.08 U/l, and the level of ASAT was 38.9±3.48 U/l, and 18.7±2.43 U/l, respectively. The difference between the average levels of ALAT and ASAT between groups is statistically significant. It was found that visual acuity in the main group prior to cataract surgery is slightly lower than in the control group. Also after the operation, in the group with patients infected with hepatitis viruses it is lower than in the group of healthy people, however, this fact did not reach the level of statistical significance. Conclusion: the study results suggest the presence of a certain relationship, if not between cataractogenesis and chronic infection with hepatitis B and C viruses, then between cataractogenesis and altered biochemical status (hyperenzymemia) with a higher probability. Key words: cataract, phacoemulsification, hepatitis B, hepatitis C. For citation: Hatsukova B.N., Chernakova G.M., Kochergin S.A. et al. Senile cataract — features of development and outcomes of surgical treatment in patients with hepatitis B and C viruses. RMJ “Clinical ophthalmology”. 2018;4:174–178.